On Neo-Thomistic Criticism of F. Nietzsche’s Ethics in Lithuania - Burnys, Zenonas (Problemos, 1981)
Some principles of ethical conceptions by F. Nietzsche revealing his relations to the Christian interpretation of ethics are presented in the article. Attempts to criticize the theoretical principles of Nietzschean ethics made by the representatives of neo-Thomistic philosophy in bourgeois Lithuania are discussed next. A conclusion is drawn that the ethical doctrines both by F. Nietzsche and his neo-Thomistic critics have no claim in being scientific ones.